The need of integrated renovation of the existing building stock in North Macedonia - Apostolska, Roberta; Shendova, Veronika; Necevska-Cvetanovska, Golubka (Informa UK Limited, 2020)
Republic of North Macedonia is a seismic prone country with a long tradition and positive experience in the field of seismic design of new and strengthening of the existing buildings up to pre-defined levels of seismic protection. The principal seismic design philosophy which is stipulated in the regulations is based on protection of human lives against strong earthquakes and partially on controlled damage due to the so called frequent earthquakes. The current construction practice generally target only one of the seven basic work requirements for construction works defined in Construction Products Regulation (CPR, 2011) i.e. mechanical resistance and stability. Starting from 2013, when the first national regulation for energy performance of the building was issued, there are some positive initiatives/ examples at national and local scale. These initiatives encompassed building capacities in construction sector in order to provide competent and qualified national workforce, necessary for achievement of national energy efficiency targets; launching the energy efficiency programs for public buildings at municipality level (pilot-project), research experimental program for developing innovative technology for earthquake resistant and energy efficiency buildings, etc. However, till today there is no integrated methodology which will target simultaneously earthquake resistance and eco-efficiency of the existing building stock in the country.
The part of the work presented in the paper was supported by the COST European Cooperation in Science and Technology, TU1104 Action: Smart Energy Region.
Keywords: Earthquake resistance; strengthening; ecoefficiency; seismic hazard; integrated renovation